Effects of Three Years of Biochar Application on Soil Organic Nitrogen Fraction in Tropical Soil - Longwei Meng; Chunlan Jiang; Meirong Huang; Qiqian Lu; Yunxing Wan; Anfu Yang; Shuirong Tang; Yanzheng Wu; Xiaoqian Dan; Qilin Zhu; Lei Meng; Ahmed S. Elrys; et al. (Agronomy)
Biochar application can increase soil carbon (C) and nitrogen (N) storage. However, the short- and long-term effects of biochar application on soil organic N fractions remain poorly understood in tropical areas. Hence, an in situ combined laboratory incubation study was investigated to determine changes in soil organic N fractions and related chemical biological properties under 1 month (BF) and 3 years (BA) of different biochar application rates (1% and 2%). The results showed that biochar application significantly increased the hydrolysable ammonium N (HAN) by 8.67–18.90% (BF) and 9.45–17.32% (BA). Amino acid N (AAN) significantly increased by 6.08–12.90% (BF) and 5.32–12.16% (BA) compared to CK. The hydrolysable unknown N decreased significantly in BF. The HAN and AAN under the higher biochar application rate were significantly higher than those under the lower application rate. Total N, HAN, and AAN contents were positively correlated with MBN. The structural equation model results showed that soil pH directly promoted AAN, and indirectly promoted soil MBC and MBN. Our results implied that the 3-year biochar application had a more stable effect on the organic N fraction. Therefore, it is possible to increase and maintain soil organic N fractions by appropriate amounts of long-term biochar application in tropical areas.